Preparation method and application of Nb2C / Ni-coated MgH2 composite material

By introducing Nb2C-MXene material and nanoNi clusters, Nb2C/Ni@MgH2 composite materials were prepared, which solved the problems of high dehydrogenation temperature, poor reversibility and insufficient cycle stability in existing hydrogen storage materials, and achieved efficient and stable hydrogen storage.

CN119706741APending Publication Date: 2025-03-28XUZHOU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510123685.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing hydrogen storage materials have problems such as high dehydrogenation temperature, poor reversibility performance, insufficient cycle stability, complex preparation process and limitations in terminal group regulation.

Method used

By introducing Nb2C-MXene material and nanoNi clusters, the interaction between metal and support was significantly enhanced, and the Nb2C/Ni@MgH2 composite material was prepared, which simplified the preparation process and improved catalytic activity and hydrogen storage performance.

Benefits of technology

The dehydrogenation temperature of MgH2 is significantly reduced, the hydrogen storage efficiency is improved, the cycle stability is enhanced, the preparation process is simplified, and a more uniform Ni cluster distribution is achieved, which improves the catalytic effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706741A_ABST
    Figure CN119706741A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an Nb2C / Ni-coated MgH2 composite material, and relates to a preparation method and application of a hydrogen storage material. The invention aims to solve the problems of high dehydrogenation temperature, poor reversibility, insufficient cycle stability, complex preparation process and limitation of terminal group regulation of the hydrogen storage material prepared in the prior art. The method comprises the following steps: 1, preparing MXene-Nb2CTx; 2, preparing an Nb2C / Ni catalyst; and 3, preparing the Nb2C / Ni-coated MgH2 composite material. The Nb2C / Ni-coated MgH2 composite material is used as a hydrogen storage material. The Nb2C-MXene material and the nano Ni cluster are introduced, so that the interaction between metal and the carrier is remarkably enhanced, and the catalytic activity and the hydrogen storage performance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a hydrogen storage material. Background Art

[0002] Existing hydrogen storage materials generally include organic liquid hydrogen storage materials, carbonaceous hydrogen storage materials, porous polymer hydrogen storage materials, metal organic framework (MOF) materials, coordinated hydride hydrogen storage materials and metal hydride hydrogen storage materials. Among them, the hydrogenation and dehydrogenation equipment of organic liquid hydrogen storage materials are expensive, the reaction conditions are harsh, the dehydrogenation efficiency is low and side reactions are easily produced, the hydrogen release rate is slow, the energy efficiency is low, the catalyst life is short, some materials are corrosive, the actual hydrogen storage density is not high, the space occupied is large, the product separation process is complicated, and it is difficult to achieve "zero emission", which limits large-scale application; the shortcomings of carbonaceous hydrogen storage materials can be summarized as low hydrogen storage capacity of activated carbon at room temperature and pressure, and slow adsorption and desorption rate. The preparation cost of carbon fiber is high, the hydrogen storage capacity needs to be improved, and the performance stability is poor. The preparation technology of carbon nanotubes is immature and costly. It relies on complex doping processes to increase hydrogen storage capacity, and doping can easily affect structural stability. Porous polymer hydrogen storage materials have prominent shortcomings. Their hydrogen storage capacity is low, making it difficult to meet large-scale hydrogen storage needs. They have poor stability and durability. After multiple cycles of hydrogen absorption and desorption, their structure is easily damaged and their performance declines. They are sensitive to environmental conditions. Factors such as temperature and humidity can affect hydrogen storage performance and service life, limiting their practical applications. Metal organic framework (MOF) materials, such as most MOF materials, have poor stability under extreme conditions such as high temperature and high humidity, and their structures are prone to collapse. The synthesis process is complex, the cost is high, and it is difficult to produce on a large scale. The hydrogen adsorption kinetics of some MOF materials are slow, the hydrogen absorption and desorption rates are not ideal, and the regeneration performance of some MOF materials is poor, which affects their reuse. The dehydrogenation reaction of coordinated hydride hydrogen storage materials usually requires high temperature, resulting in high energy consumption. The rehydrogenation process of the product after dehydrogenation is difficult and the reversibility is poor. Some materials contain rare metals, which are costly and scarce. The materials have poor hydrogen absorption and desorption kinetics and slow reaction rates. In addition, there may be safety issues, such as poor thermal stability, which can easily cause danger. Metal hydride hydrogen storage materials also have many disadvantages. The hydrogen absorption and desorption temperatures are high, which increases energy consumption and equipment requirements. The equilibrium pressure is affected by many factors. The hydrogen desorption pressure is low at room temperature. The operation and control are difficult and the hydrogen absorption and desorption speed is slow, which affects the utilization efficiency. The activation process is complicated and increases the use cost.

[0003] Therefore, the hydrogen storage materials prepared by the prior art have the problems of high dehydrogenation temperature, poor reversibility performance, insufficient cycle stability, complex preparation process and limited end group regulation. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of high dehydrogenation temperature, poor reversibility, insufficient cycle stability, complex preparation process and limitation of end group regulation in hydrogen storage materials prepared by prior art, and to provide a Nb 2C / Ni@MgH 2 Preparation methods and applications of composite materials.

[0005] The present invention introduces Nb 2 C-MXene materials and nano-Ni clusters significantly enhance the interaction between metal and support, and improve the catalytic activity and hydrogen storage performance.

[0006] A Nb 2 C / Ni@MgH 2 The preparation method of the composite material is specifically completed according to the following steps:

[0007] 1. Preparation of MXene-Nb 2 CT x :

[0008] Add LiF and HCl solution into the reactor, stir until bubbles stop forming, let it stand for a while, and then add Nb 2 AlC powder was added to the reactor for etching; after the etching was completed, it was centrifuged and filtered, and the collected solid matter was washed with water several times and dried to obtain MXene-Nb 2 CT x ;

[0009] 2. Preparation of Nb 2 C / Ni catalyst:

[0010] MXene-Nb 2 CT x Add tetrahydrofuran, then add nickel tetracarbonyl, heat and ultrasonicate for a period of time, filter, dry the solid matter to obtain a reaction product; 2 / Ar atmosphere, and then cooled to room temperature to obtain Nb 2 C / Ni catalyst;

[0011] 3. Preparation of Nb 2 C / Ni@MgH 2 Composite Materials:

[0012] Nb 2 C / Ni catalyst and MgH 2 Mix and high-speed ball mill for a period of time to obtain Nb 2 C / Ni@MgH 2 Composite materials.

[0013] A Nb 2 C / Ni@MgH 2 Composite materials are used as hydrogen storage materials.

[0014] Advantages of the present invention:

[0015] 1. The existing technology has the problem of high dehydrogenation temperature in hydrogen storage applications, resulting in high energy consumption. The present invention introduces nano-Ni clusters and Nb 2 C-MXene material significantly reduces the MgH 2 The dehydrogenation temperature is increased, and the hydrogen storage efficiency is improved; after multiple cycles, the hydrogen storage capacity of some composite materials will decrease significantly. The Nb prepared by the present invention 2 C / Ni@MgH 2 The composite material exhibits excellent cycling stability and reduced capacity fading;

[0016] Second, the preparation method of the present invention is relatively simple, avoiding the complicated multi-step reaction in the prior art, and improving the preparation efficiency and material purity;

[0017] 3. The present invention regulates Nb 2 The end groups of C-MXene materials (such as -F and -O) achieve a more uniform distribution of Ni clusters, enhance the catalytic effect, and solve the problem of limited regulation effect of end groups in the prior art;

[0018] 4. Nb used in the present invention 2 The C / Ni catalyst significantly enhances the interaction between the metal and the carrier, improves the catalytic activity, and solves the problem in existing catalysts that the interaction between the metal and the carrier is not strong enough, resulting in limited catalytic effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Nb prepared in Example 1 and Comparative Examples 1 to 4 2 CT x XRD spectrum of

[0020] Figure 2 The Nb prepared in Example 1 2 C、Nb 2 C / Ni and Nb 2 C / Ni@MgH 2 XRD spectra of the composite materials;

[0021] Figure 3 The Nb prepared in Example 1 2 SEM image and EDS spectrum of C / Ni catalyst;

[0022] Figure 4 The Nb prepared in Example 1 2 C / Ni@MgH 2 SEM images and EDS spectra of the composite materials;

[0023] Figure 5 The Nb prepared in Example 1 2 C / Ni@MgH2 HAADF-STEM images and EDS spectra of the composites;

[0024] Figure 6 The XPS spectrum diagram, d to g in the figure are Nb prepared in Example 1 2 C / Ni and Nb 2 C / Ni@MgH 2 XPS spectrum of the composite material, Nb 3d, Nb 3d, O 1s, F 1s; hi is the Nb prepared in Example 1 2 C / Ni and Nb 2 C / Ni@MgH 2 XPS spectra of the composites at 650 °C: Ni 2p, Mg 1s;

[0025] Figure 7 The Nb prepared in Example 1 2 C / Ni@MgH 2 The hydrogenation process of the composite material, b and c are Nb prepared in Example 1 2 C / Ni@MgH 2 Hydrogen adsorption cycles of the composite materials at 80, 140, 200 and 300 °C. d is the hydrogen adsorption cycle of the Nb prepared in Example 1 observed at 200 °C. 2 C / Ni@MgH 2 The hydrogen absorption and desorption rates of the composite materials, e and f are observed at 200 °C for the Nb prepared in Example 1. 2 C / Ni@MgH 2 The hydrogen absorption and desorption rates of the composite materials, g, are the hydrogen absorption and desorption rates of the Nb prepared in Example 1 observed at 200 °C. 2 C / Ni@MgH 2 The composite material has a stable dehydrogenation mass fraction of about 6.8wt% in multiple hydrogen absorption and dehydrogenation cycle curves, and h is the Nb prepared in Example 1 observed at 140°C. 2 C / Ni@MgH 2 The hydrogen absorption and desorption rates of the composites are those observed for pure MgH at 200 °C. 2 The hydrogen absorption and desorption rates. DETAILED DESCRIPTION

[0026] Specific implementation method 1: In this implementation method, a Nb 2 C / Ni@MgH 2 The preparation method of the composite material is specifically completed according to the following steps:

[0027] 1. Preparation of MXene-Nb 2 CT x :

[0028] Add LiF and HCl solution into the reactor, stir until bubbles stop forming, let it stand for a while, and then add Nb 2 AlC powder was added to the reactor for etching; after the etching was completed, it was centrifuged and filtered, and the collected solid matter was washed with water several times and dried to obtain MXene-Nb 2 CT x ;

[0029] 2. Preparation of Nb 2 C / Ni catalyst:

[0030] MXene-Nb 2 CT x Add tetrahydrofuran, then add nickel tetracarbonyl, heat and ultrasonicate for a period of time, filter, dry the solid matter to obtain a reaction product; 2 / Ar atmosphere, and then cooled to room temperature to obtain Nb 2 C / Ni catalyst;

[0031] 3. Preparation of Nb 2 C / Ni@MgH 2 Composite Materials:

[0032] Nb 2 C / Ni catalyst and MgH 2 Mix and high-speed ball mill for a period of time to obtain Nb 2 C / Ni@MgH 2 Composite materials.

[0033] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that: the LiF, Nb 2 The mass volume ratio of AlC powder to HCl solution is (0.8 g to 1.2 g): (0.9 g to 1.1 g): (18 mL to 22 mL); the mass fraction of the HCl solution in step 1 is 37%. The other steps are the same as those in the first embodiment.

[0034] Specific implementation method three: The difference between this implementation method and specific implementation method one or two is that: the temperature of the etching solution described in step one is 80° C. to 100° C.; the etching time described in step one is 70 h to 75 h.

[0035] The other steps are the same as those in the first or second embodiment.

[0036] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the centrifugal speed in step 1 is 3000 r / min, the centrifugal time is 2 min to 4 min; the collected solid matter is washed 3 to 5 times with deionized water in step 1. The other steps are the same as those in specific embodiments 1 to 3.

[0037] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that the drying temperature in step 1 is 80°C to 100°C and the standing time in step 1 is 5 minutes to 15 minutes. The other steps are the same as those in specific implementation methods 1 to 4.

[0038] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the MXene-Nb 2 CT x The mass volume ratio of tetrahydrofuran and nickel tetracarbonyl is (1 g to 2 g): (28 mL to 32 mL): (0.3 g to 0.54 g). The other steps are the same as those in the first to fifth embodiments.

[0039] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the heating and ultrasonic treatment time in step 2 is 0.5 h to 1 h, and the heating temperature is 30° C. to 50° C. The other steps are the same as those of specific embodiments 1 to 6.

[0040] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that: the temperature for drying the solid material in step 2 is 80°C to 100°C; the H 2 The volume ratio of hydrogen to argon in the / Ar atmosphere is 1:6; the temperature of the high temperature calcination in step 2 is 600°C to 700°C, and the time of the high temperature calcination is 2h to 3h. The other steps are the same as those in specific embodiments 1 to 7.

[0041] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: Nb in step 3 2 C / Ni catalyst and MgH 2 The mass ratio of is 1:(2-4); the speed of the high-speed ball milling in step 3 is 500r / min-600r / min, and the time of the high-speed ball milling is 1h-2h. The other steps are the same as those in specific embodiments 1 to 8.

[0042] Specific implementation method ten: This implementation method is a Nb 2 C / Ni@MgH 2 Composite materials are used as hydrogen storage materials.

[0043] The following examples are used to verify the beneficial effects of the present invention:

[0044] Example 1: A Nb 2 C / Ni@MgH 2 The preparation method of the composite material is specifically completed according to the following steps:

[0045] 1. Preparation of MXene-Nb 2 CT x :

[0046] 1.0 g LiF and 20 mL 37% HCl solution were added to the reactor and stirred until bubbles stopped forming. After standing for 10 min, 1.0 g Nb 2 AlC powder was added into the reactor for etching at 80°C for 72h. After the etching was completed, the solid was centrifuged and filtered. The collected solid was washed three times with deionized water and then dried at 100°C to obtain MXene-Nb 2 CT x ;

[0047] The centrifugal speed in step 1 is 3000 r / min, and the centrifugal time is 3 min;

[0048] 2. Preparation of Nb 2 C / Ni catalyst:

[0049] MXene-Nb 2 CT x Add tetrahydrofuran, then add nickel tetracarbonyl, heat and ultrasonicate for a period of time, filter, dry the solid matter to obtain a reaction product; 2 / Ar atmosphere, and then cooled to room temperature to obtain Nb 2 C / Ni catalyst;

[0050] The MXene-Nb 2 CT x , the mass volume ratio of tetrahydrofuran and nickel tetracarbonyl is 2g:30mL:0.4g;

[0051] The heating and ultrasonic treatment time in step 2 is 0.5 h, and the heating temperature is 30° C.

[0052] The temperature for drying the solid matter in step 2 is 100°C;

[0053] H described in step 2 2 / The volume ratio of hydrogen to argon in the Ar atmosphere is 1:6;

[0054] The high temperature calcination temperature in step 2 is 650°C, and the high temperature calcination time is 2h;

[0055] 3. Preparation of Nb 2 C / Ni@MgH 2 Composite Materials:

[0056] Nb 2 C / Ni catalyst and MgH 2 Mix and high-speed ball mill for a period of time to obtain Nb 2 C / Ni@MgH 2 Composite material (denoted as Nb-HCl-1.0g LiF-72h-80℃).

[0057] Nb described in step 3 2 C / Ni catalyst and MgH 2 The mass ratio is 1:3;

[0058] The speed of the high-speed ball mill described in step 3 is 500 r / min, and the time of the high-speed ball mill is 1 h.

[0059] Comparative Example 1: The difference between this comparative example and Example 1 is that in step 1, 1.0 g LiF and 20 mL of 37% HF solution are added to the reactor, stirred until bubbles stop forming, and allowed to stand for 10 min. Then, 1.0 g Nb 2 AlC powder was added into the reactor for etching at a temperature of 80°C and a time of 72h. The Nb 2 C / Ni@MgH 2 The composite material is recorded as Nb-HCl-1.0 g HF-72 h-80° C. Other steps and parameters are the same as those in Example 1.

[0060] Comparative Example 2: The difference between this comparative example and Example 1 is that in step 1, 1.0 g LiF and 20 mL of 37% HF solution are added to the reactor, stirred until bubbles stop forming, and allowed to stand for 10 min. Then, 1.0 g Nb 2 AlC powder was added into the reactor for etching at a temperature of 100°C and a time of 72h. The Nb 2 C / Ni@MgH 2 The composite material is recorded as Nb-HCl-1.0 g LiF-72 h-100° C. Other steps and parameters are the same as those in Example 1.

[0061] Comparative Example 3: The difference between this comparative example and Example 1 is that in step 1, 1.0 g LiF and 20 mL of 37% HF solution are added to the reactor, stirred until bubbles stop forming, and allowed to stand for 10 min. Then, 1.0 g Nb 2 AlC powder was added into the reactor for etching at a temperature of 180°C and a time of 72h. The Nb 2 C / Ni@MgH 2 The composite material is recorded as Nb-HCl-1.0 g LiF-72 h-180° C. Other steps and parameters are the same as those in Example 1.

[0062] Comparative Example 4: The difference between this comparative example and Example 1 is that in step 1, 0.8 gg LiF and 20 mL of 37% HF solution are added to the reactor, stirred until bubbles stop forming, and allowed to stand for 10 min. Then, 1.0 g Nb 2 AlC powder was added into the reactor for etching at a temperature of 180°C and a time of 72h. The Nb 2 C / Ni@MgH 2 The composite material is recorded as Nb-HCl-0.8 g LiF-72 h-180° C. Other steps and parameters are the same as those in Example 1.

[0063] Figure 1 Nb prepared in Example 1 and Comparative Examples 1 to 4 2 CT x XRD spectrum of

[0064] from Figure 1 It can be seen that: etching Nb 2 CT x The best method is to use 1.0 g LiF-20 mL HCl solution at 80° C. for 72 h, which is the method of Example 1.

[0065] Figure 2 The Nb prepared in Example 1 2 C、Nb 2 C / Ni and Nb 2 C / Ni@MgH 2 XRD spectra of the composite materials;

[0066] from Figure 2 It can be seen that: XRD results confirm the formation of the target material, these findings prove that the synthesis method is effective for Nb 2 C / Ni catalyst and Nb 2 C / Ni@MgH 2 Effectiveness of composite materials.

[0067] Figure 3 The Nb prepared in Example 1 2 SEM image and EDS spectrum of C / Ni catalyst;

[0068] from Figure 3 It can be seen that nano-Ni in 2D Nb 2 CT x The surface is uniformly dispersed and shows signals corresponding to the elements Nb, Ni and C.

[0069] Figure 4 The Nb prepared in Example 1 2 C / Ni@MgH 2 SEM images and EDS spectra of the composite materials;

[0070] from Figure 4 It can be seen that: the spectrum shows the presence of Nb, Ni and Mg, and the catalyst prepared in Example 1 is uniformly dispersed in MgH 2 middle.

[0071] Figure 5 The Nb prepared in Example 1 2 C / Ni@MgH 2 HAADF-STEM images and EDS spectra of the composites;

[0072] from Figure 5 The flake structure can be clearly observed, and the results confirm that Ni and MgH 2 Evenly distributed in Nb 2 CT x surface.

[0073] Figure 6 The XPS spectrum diagram, d to g in the figure are Nb prepared in Example 1 2 C / Ni and Nb 2 C / Ni@MgH 2 XPS spectrum of the composite material, Nb 3d, Nb 3d, O 1s, F 1s; hi is the Nb prepared in Example 1 2 C / Ni and Nb 2 C / Ni@MgH 2 XPS spectra of the composites at 650 °C: Ni 2p, Mg 1s;

[0074] from Figure 6 It can be seen that high temperature treatment retains the 2D Nb 2 CT x The structure of the CF and Nb-F bonds did not change significantly.

[0075] Figure 7 The Nb prepared in Example 1 2 C / Ni@MgH2 The hydrogenation process of the composite material, b and c are Nb prepared in Example 1 2 C / Ni@MgH 2 Hydrogen adsorption cycles of the composite materials at 80, 140, 200 and 300 °C. d is the hydrogen adsorption cycle of the Nb prepared in Example 1 observed at 200 °C. 2 C / Ni@MgH 2 The hydrogen absorption and desorption rates of the composite materials, e and f are observed at 200 °C for the Nb prepared in Example 1. 2 C / Ni@MgH 2 The hydrogen absorption and desorption rates of the composite materials, g, are the hydrogen absorption and desorption rates of the Nb prepared in Example 1 observed at 200 °C. 2 C / Ni@MgH 2 The composite material has a stable dehydrogenation mass fraction of about 6.8wt% in multiple hydrogen absorption and dehydrogenation cycle curves, and h is the Nb prepared in Example 1 observed at 140°C. 2 C / Ni@MgH 2 The hydrogen absorption and desorption rates of the composites are those observed for pure MgH at 200 °C. 2 The hydrogen absorption and desorption rates;

[0076] from Figure 7 It can be seen that: Nb prepared in Example 1 2 C / Ni@MgH 2 The composite material maintained its hydrogen storage capacity effectively during multiple hydrogenation and dehydrogenation cycles. Both the amount of hydrogen and the absorption / desorption rate gradually increased with temperature, showing the best hydrogen storage capacity at 200°C and the highest absorption / desorption rate at 300°C. Isothermal hydrogenation and dehydrogenation tests at 200°C highlighted the potential of the composite material for practical hydrogen storage applications.

Claims

1. A method for preparing a Nb2C / Ni@MgH2 composite material, characterized in that The preparation method is specifically completed according to the following steps:

1. Preparation of MXene-Nb2CT x : LiF and HCl solution were added to the reactor, stirred until bubbles stopped forming, and allowed to stand for a while. Nb2AlC powder was then added to the reactor for etching. After etching, the mixture was centrifuged and filtered, and the collected solid matter was washed with water several times and dried to obtain MXene-Nb2CT. x ; 2. Preparation of Nb2C / Ni catalyst: MXene-Nb2CT x adding tetrahydrofuran, then adding nickel tetracarbonyl, heating and ultrasonic treatment for a period of time, filtering, and drying the solid matter to obtain a reaction product; calcining the reaction product at high temperature under H2 / Ar atmosphere, and cooling to room temperature to obtain a Nb2C / Ni catalyst; 3. Preparation of Nb2C / Ni@MgH2 composite materials: The Nb2C / Ni catalyst was mixed with MgH2 and subjected to high-speed ball milling for a period of time to obtain a Nb2C / Ni@MgH2 composite material.

2. The method for preparing a Nb2C / Ni@MgH2 composite material according to claim 1, characterized in that The mass volume ratio of LiF, Nb2AlC powder and HCl solution described in step 1 is (0.8g~1.2g):(0.9g~1.1g):(18mL~22mL); the mass fraction of the HCl solution described in step 1 is 37%.

3. The method for preparing a Nb2C / Ni@MgH2 composite material according to claim 1, characterized in that The temperature of the etching solution in step 1 is 80° C. to 100° C.; the etching time in step 1 is 70 h to 75 h.

4. The method for preparing a Nb2C / Ni@MgH2 composite material according to claim 1, characterized in that The centrifugal speed in step 1 is 3000 r / min, and the centrifugal time is 2 min to 4 min. The collected solid matter in step 1 is washed 3 to 5 times with deionized water.

5. The method for preparing a Nb2C / Ni@MgH2 composite material according to claim 1, characterized in that The drying temperature in step 1 is 80° C. to 100° C.; the standing time in step 1 is 5 min to 15 min.

6. The method for preparing a Nb2C / Ni@MgH2 composite material according to claim 1, characterized in that MXene-Nb2CT as described in step 2 x , tetrahydrofuran and nickel tetracarbonyl ratio is (1g~2g):(28mL~32mL):(0.3g~0.54g).

7. The method for preparing a Nb2C / Ni@MgH2 composite material according to claim 1, characterized in that The time of heating and ultrasonic treatment in step 2 is 0.5h to 1h, and the heating temperature is 30°C to 50°C.

8. The method for preparing a Nb2C / Ni@MgH2 composite material according to claim 1, characterized in that The temperature for drying the solid material in step 2 is 80°C to 100°C; the volume ratio of hydrogen to argon in the H2 / Ar atmosphere in step 2 is 1:6; the temperature of high-temperature calcination in step 2 is 600°C to 700°C, and the time of high-temperature calcination is 2h to 3h.

9. The method for preparing a Nb2C / Ni@MgH2 composite material according to claim 1, characterized in that The mass ratio of the Nb2C / Ni catalyst to MgH2 described in step three is 1:(2-4); the speed of the high-speed ball mill described in step three is 500r / min-600r / min, and the time of the high-speed ball mill is 1h-2h.

10. Application of a Nb2C / Ni@MgH2 composite material prepared by the preparation method according to claim 1, characterized in that A Nb2C / Ni@MgH2 composite material is used as a hydrogen storage material.